Integrating Multicultural Values in Islamic Religious Education: A Case Study in Junior High Schools - Mustamir Mustamir; Muhammad Tang (AL-ISHLAH: Jurnal Pendidikan, 2025)
Multicultural education aims to ensure fair representation of diverse social groups in school curricula, particularly those historically marginalized due to gender, race, class, or religion. Islamic religious education (IRE) in schools and madrasas emphasizes strengthening faith through knowledge, appreciation, practice, and student experiences. This study examines the contribution of IRE in fostering multicultural tolerance and solidarity among students. This study employed a qualitative approach with a case study method to explore the implementation of multicultural values in schools. Data were collected through observations, interviews, and document analysis. The focus was on the role of schools and Islamic religious education teachers in promoting tolerance and solidarity. The findings indicate that IRE contributes to multicultural tolerance through two key strategies: a) Religious and Social Activities – Schools and IRE teachers organize activities such as social donations during disasters, fostering solidarity. Extracurricular activities, including futsal, scouts, and choirs, further support the development of tolerance. b) Good Habits in the School Environment – IRE teachers encourage respect for differences and collaboration among students, promoting daily habits that reinforce multicultural values. These findings suggest that Islamic religious education plays a significant role in strengthening multicultural values by integrating religious teachings with social practices that promote inclusivity and cooperation. Islamic religious education, through religious activities, social engagement, and good habits, fosters multicultural tolerance and solidarity among students. Schools should continue integrating these values into their educational practices to strengthen social cohesion in diverse learning environments.